Chapter Where Alice fell into Motion events from a parallel corpus - Verkerk, Annemarie (De Gruyter, 2014)
The way in which different languages encode motion has been an important topic of investigation in the last few decades. As more data from typologically different languages has become available, the strict dichotomy between satellite-framed and verb-framed languages proposed by Talmy (1985, 1991, 2000) has come under fire (Croft et al. 2010; Beavers et al. 2010). Drawing on a parallel corpus with data from sixteen Indo-European languages, this paper investigates the validity of these categories. I employ aggregation measures to present visual representations of the relationships between the languages in order to show that although some languages fit well into the category of "satellite-framed" or "verb-framed" language, others clearly do not. In line with these and other results, I propose that the Talmyan classifications only have limited use, and motion research should take into account all motion construction types when describing motion encoding.